2021
DOI: 10.4102/sajp.v77i1.1559
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with balance impairments amongst stroke survivors in northern Benin: A cross-sectional study

Abstract: Background: Balance impairment is the predominant risk factor for falls in stroke survivors. A fear of falling after stroke can contribute to sedentary lifestyles, increased disability and risk of recurrence, leading to poor quality of life.Objective: To determine the frequency and factors associated with balance impairments amongst stroke survivors at the University Hospital of Parakou.Method: This cross-sectional study included adult stroke survivors. Stroke survivors after discharge were enrolled at the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…and equitably accessible rehabilitation services in low-and middle-income countries (Bernhardt et al 2020). Studies examining the frequency of balance impairments following a stroke (Chang, Gajasinghe & Arambepola 2015;Kossi et al 2021;Vincent-Onabajo, Musa & Joseph 2018) have reported prevalence rates ranging from 16.7% (Vincent-Onabajo et al 2018) to as high as 83% (Chang et al 2015;Kossi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and equitably accessible rehabilitation services in low-and middle-income countries (Bernhardt et al 2020). Studies examining the frequency of balance impairments following a stroke (Chang, Gajasinghe & Arambepola 2015;Kossi et al 2021;Vincent-Onabajo, Musa & Joseph 2018) have reported prevalence rates ranging from 16.7% (Vincent-Onabajo et al 2018) to as high as 83% (Chang et al 2015;Kossi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the second leading cause of death and a major cause of disability worldwide (Katan & Luft 2018). Disability because of stroke is still very common up to three years after the event (Kossi et al 2021). In a 2016 meta-analysis, the total prevalence rate for stroke in Africa was estimated to be 3.5 cases per 1000 people, with an annual increasing trend of 12.0% (Ezejimofor et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balance disorders are recurrent problems in stroke survivors, which could directly affect walking capacity, leading to a poor quality of life (QoL) (Kossi et al 2021;Schmid et al 2013). The main causes of poor balance after a stroke are impaired muscle coordination and loss of sensation on the affected side, especially in the legs and trunk (Aries et al 2022;Gath et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of persons with disabilities who experience stroke is gradually increasing (Adoukonou et al, 2020). Loss of balance while walking is common after stroke (Chang et al, 2021;Kossi et al, 2021), with about 70% of people living at home post stroke reporting a fall within a year of their stroke (Beyaert et al, 2015;Kossi et al, 2021). Limited walking capacity restricts the person's independent mobility and can contribute to a sedentary lifestyle, increased disability and risk of recurrence, resulting in a poorer quality of life (Nindorera et al, 2021;Schmid et al, 2013).Previous studies have shown that motor function, balance, walking capacity and independence in activities of daily living are of importance for perceived health-related QoL (Langhammer et al, 2008(Langhammer et al, , 2014Nindorera et al, 2021).Better quality of life has been reported to be associated with greater independence in daily living and mobility (Heikinheimo & Chimbayo, 2015).…”
Section: Introductionmentioning
confidence: 99%